Development of fatal intestinal inflammation in MyD88 deficient mice co-infected with helminth and bacterial enteropathogens. - Libo Su; Yujuan Qi; Mei Zhang; Meiqian Weng; Xichen Zhang; Chienwen Su; Hai Ning Shi (Public Library of Science (PLoS), 2014)
Infections with intestinal helminth and bacterial pathogens, such as enteropathogenic Escherichia coli, continue to be a major global health threat for children. To determine whether and how an intestinal helminth parasite, Heligomosomoides polygyrus, might impact the TLR signaling pathway during the response to a bacterial enteropathogen, MyD88 knockout and wild-type C57BL/6 mice were infected with H. polygyrus, the bacterial enteropathogen Citrobacter rodentium, or both. We found that MyD88 knockout mice co-infected with H. polygyrus and C. rodentium developed more severe intestinal inflammation and elevated mortality compared to the wild-type mice. The enhanced susceptibility to C. rodentium, intestinal injury and mortality of the co-infected MyD88 knockout mice were found to be associated with markedly reduced intestinal phagocyte recruitment, decreased expression of the chemoattractant KC, and a significant increase in bacterial translocation. Moreover, the increase in bacterial infection and disease severity were found to be correlated with a significant downregulation of antimicrobial peptide expression in the intestinal tissue in co-infected MyD88 knockout mice. Our results suggest that the MyD88 signaling pathway plays a critical role for host defense and survival during helminth and enteric bacterial co-infection.